A pilot study to investigate the therapeutic effect of Valsalva maneuver on otitis media with effusion in adults. Issue 1 (February 2019) - Han, Jung Ju; Park, Jung Mee; Kim, Dong Kee; Park, So Young; Park, Shi Nae
Abstract: Objective: This pilot study was performed to investigate the therapeutic effect of Valsalva maneuver on otitis media in adults and to evaluate the prognostic factors for the good response. Methods: Thirty nine ears of 32 adult patients who were diagnosed as otitis media with effusion and managed by one-week Valsalva maneuver (>20/day) without any other medication were included in this study. Its therapeutic efficacy was evaluated and the prognostic factors which predict the response of Valsalva maneuver were analyzed by comparing various clinical and audiological factors between success and failure groups. Results: Mean duration of otitis media in the study subjects was 30.9 days (SD 31.6 days). A success rate of 1-week Valsalva maneuver as a single therapeutic modality was up to 64.1% (25/39 ears) and hearing was significantly recovered in success group. No recurrence or side effects were observed. Successful Valsalva maneuver checked and confirmed as bulging of the tympanic membrane by otoendoscopic examination was an excellent indicator of therapeutic response in a week (p < 0.05). Age, sex, duration of otitis media, history of previous upper respiratory tract infection, initial hearing levels and type of audiogram were not significant prognostic factors for the therapeutic efficacy of Valsalva maneuver. Conclusion: One-week Valsalva maneuver seems to be considered as a first line therapeutic modality in otitis media with effusion in adult patients who demonstrate the successful maneuver result on oto-endoscopic examination.